FAKTOR YANG MEMENGARUHI STRUKTUR MODAL PERUSAHAAN MANUFAKTUR - Setiawan, Bryan; Nugroho, Vidyarto (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This study aims to determine the effect of asset structure, firm size, liquidity, profitability, and sales growth on capital structure in manufacturing companies listed on the Indonesia Stock Exchange during 2017-2019 period. Purposive sampling was used as the sampling technique and obtained as many as 43 companies. Data processing using EViews software version 12. The analysis technique used in this research is multiple linear regression analysis. The results of the study found that asset structure has no effect on capital structure. Firm size has a positive effect on capital structure. Liquidity has a negative effect on capital structure. Profitability has no effect on capital structure. Sales Growth has no effect on capital structure.